2003
DOI: 10.1038/sj.mp.4001322
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan of Arab Israeli families maps a schizophrenia susceptibility gene to chromosome 6q23 and supports a locus at chromosome 10q24

Abstract: is a complex neuropsychiatric disorder to which an as-yet-unknown number of genes contribute, interacting with each other and the environment. Linkage analyses have implicated several chromosomal regions as harboring schizophrenia susceptibility loci although rarely at levels commensurate with proposed thresholds for genome-wide significance. We systematically recruited Arab Israeli families multiply affected with schizophrenia from the catchment area of a Regional Mental Health Center. Clinical diagnoses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
109
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 41 publications
6
109
0
1
Order By: Relevance
“…These analyses (details available on request) indicated that our sample has a power (1Àb) X80%, with the exception of cases where the GenAF is lower than 0.15. Allelic stratification is unlikely in our homogeneous population, and the previous results from linkage analyses in our population 8,9 render estimates for a GenAF < 0.2 improbable. Nevertheless, the power to detect a positive association holds if the association is present only in 40% of the sample for a gene showing a GenAF X0.2.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…These analyses (details available on request) indicated that our sample has a power (1Àb) X80%, with the exception of cases where the GenAF is lower than 0.15. Allelic stratification is unlikely in our homogeneous population, and the previous results from linkage analyses in our population 8,9 render estimates for a GenAF < 0.2 improbable. Nevertheless, the power to detect a positive association holds if the association is present only in 40% of the sample for a gene showing a GenAF X0.2.…”
mentioning
confidence: 68%
“…8,9 Our peak linkage was at 136.3 Mb rendering TRAR4 (at 132.9 Mb) a viable positional candidate. In fact, TRAR4 is considerably closer to the linkage peak in our sample than to the more diffuse signal observed in the samples found to be associated with TRAR4.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…5 A number of other groups have found evidence of linkage of BPAD and/or SCZ to this 4p region as well. Asherson et al 6 reported linkage in a schizoaffective family (F50, LOD = 2.0); Ewald et al 7 reported linkage in BPAD families (LOD = 2.0); Detera-Wadleigh et al 8 investigated families with major mental illness, and their largest family (F48) generated an LOD of 3.2; Williams et al 9 found increased sharing in SCZ sibpairs (LOD = 1.7); Lerer et al 10 found a non-parametric LOD score of 2.2 in families with SCZ and schizoaffective disorder; and Als et al 11 found excess haplotype sharing (best P-value, P = 0.00007) in families with BPAD and SCZ.…”
Section: Introductionmentioning
confidence: 99%